2014
DOI: 10.1002/jps.24213
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Liberation of Indomethacin from Chitosan Gels Containing Microemulsion in Different Dissolution Mediums

Abstract: The objective of this research is to outline the liberation of indomethacin from different chitosan gels containing O/W microemulsion. The influence of surfactant, sodium lauryl sulfate, in two concentrations (0.5% and 0.75%, w/w) was determined in dissolution medium on the release of indomethacin, which was used as poor water-soluble model drug. Chitosan gels were prepared in four different concentrations of chitosan-1%, 1.5%, 2%, and 3% (w/w). Microemulsion enhanced the liberation of the indomethacin from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Based on the best goodness of fit (see Table 5), it was found that MG 3 , MG 4 , and the marketed product were followed Higuchi kinetic model (MG 3 : R 2 = 0.9942, MG 4 : R 2 = 0.9862, marketed gel: R 2 = 0.9832). Higuchi model-based permeation, previously reported for indomethacin (chitosan-based), terbinafine (chitosan-based), itraconazole (Lutrol ® F127based) and ibuprofen (Carbopol ® 940-based) MBGs and for topical ketoprofen and pentoxifylline MEs (24,(60)(61)(62)(63)(64), suggests that the release process could be mainly controlled by the Fickian diffusion of dissolved lidocaine through the gel network of Carbomer ® 940. However, the analysis of the release plot for MG5 revealed that lidocaine followed the first-order model for controlled permeation, suggesting that the release rate is concentration-dependent (23,65).…”
Section: Drug Release Kineticsmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on the best goodness of fit (see Table 5), it was found that MG 3 , MG 4 , and the marketed product were followed Higuchi kinetic model (MG 3 : R 2 = 0.9942, MG 4 : R 2 = 0.9862, marketed gel: R 2 = 0.9832). Higuchi model-based permeation, previously reported for indomethacin (chitosan-based), terbinafine (chitosan-based), itraconazole (Lutrol ® F127based) and ibuprofen (Carbopol ® 940-based) MBGs and for topical ketoprofen and pentoxifylline MEs (24,(60)(61)(62)(63)(64), suggests that the release process could be mainly controlled by the Fickian diffusion of dissolved lidocaine through the gel network of Carbomer ® 940. However, the analysis of the release plot for MG5 revealed that lidocaine followed the first-order model for controlled permeation, suggesting that the release rate is concentration-dependent (23,65).…”
Section: Drug Release Kineticsmentioning
confidence: 83%
“…A quantity of 200 mg of the gel was applied to the membrane, and the donor chamber was covered with Parafilm ® . At predetermined time intervals (5,7,10,15,20,30,45,60,75,90,105, and 120 min), an aliquot of 2 mL sample was taken from the release medium, and the same volume of the fresh buffer was added to the receptor chamber to maintain the sink condition. During the test, the diffusion cells were checked for the presence of a bubble on both sides of the membrane.…”
Section: Cellulose Acetate Membranementioning
confidence: 99%
“…Various types of mathematical models have been used to determine the kinetics of drug release from the delivery systems, such as zero order, first order, and Higuchi model ( Starychova et al., 2014 ; Zandi, 2017 ). These dissolution models are necessary to study the release mechanism of drugs, as it mathematically describes the release profiles, such as the release of VC.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan exhibits many excellent properties, such as biocompatibility, non-toxicity, biodegradability, particular solubility, along with antimicrobial [ 135 , 136 ], antioxidant [ 137 ], antiviral, and antifungal effects [ 138 ]. Chitosan is well known as an excipient for drop-type ophthalmic products [ 139 ], and also for complex entities like liposomes [ 140 ], microemulsions [ 141 ], hydrogels [ 142 ], and implants [ 143 ]. Due to its excellent characteristics, chitosan can be used as a scaffold alone or in association with other polymers to develop new materials with promising biomedical uses.…”
Section: Bacterial Cellulose Composites—important Emerging Materials ...mentioning
confidence: 99%